Feasibility trial protocol assessing the use of aerobic exercise to promote recovery from work-related concussion - Jacob I. McPherson; Jeffrey C. Miecznikowski; Haley Chizuk; Patrick Sparks; John J. Leddy; Mohammad N. Haider; Christopher J. Stavisky (PLoS ONE, 2025)
Introduction Work-related concussion (WRC) is a common occupational injury that has received far less research attention compared to sport-related concussion (SRC). WRC results in prolonged lost time claims, adversely influences perceived life roles, and negatively impacts personal and family finances. WRC also affects workforce capacity in industries that are already facing worker shortages (e.g., construction, manufacturing, healthcare, etc.). Targeted heart rate aerobic exercise (THRAE) has emerged as an effective treatment for speeding recovery from SRC and for reducing the incidence of persisting post-concussive symptoms (PPCS). The aim of this proposed study is to explore the feasibility of THRAE in adults with WRC as there are very few interventions that have been rigorously studied in this population. Materials and Methods We describe a feasibility trial to implement THRAE in individuals with WRC. While this study will not test specific hypotheses related to effectiveness, it will provide key information related to adherence, safety, and psychosocial factors related to adherence and participation. Additionally, this study will provide mean and standard deviation values for the measures applied to this novel population to inform power analyses for larger-scale trials. Trial registration Clinicaltrials.gov NCT06263179